Strategi Guru PAI dalam Menumbuhkan Rasa Cinta Tanah Air - Rahmatullah, Asep; Maulana, M. Iqbal (Pelita: Jurnal Studi Islam Mahasiswa UII Dalwa, 2023)
Indonesia is a heterogeneous country or is often said to be a pluralistic country. Because the country of Indonesia has very unique advantages, it can be seen from the condition of the country of Indonesia with a population of approximately 250 million people, each with its own diversity. This research uses a qualitative approach with a descriptive approach. The formation of student character is an ongoing process that involves the important roles of schools, families and communities. Teachers play a central role in shaping student character because they interact continuously with students in the school environment. They can influence and shape students' character through daily interactions, observations, and moral education. Apart from teachers, school rules and regulations also have an important role in forming students' character.